2003
DOI: 10.1046/j.0038-4941.2003.08404014.x
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Structure of Structural Assimilation: White‐Collar Mexican Ethnicity and the Significance of Ethnic Identity Professional Organizations*

Abstract: Objective. This article examines the experience of ethnicity among third‐plus generation Mexican‐American professionals at the workplace and through participation in ethnic identity professional organizations. Methods. A total of 25 face‐to‐face interviews were conducted in the San Jose, California metro area. Interviewees were initially recruited from two ethnic identity professional organizations. Results. The predicted confluence of acculturation with structural assimilation is supported by the responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
(19 reference statements)
2
2
0
Order By: Relevance
“…Both these communities are semi-rural, and Mexican Americans are predominantly an urban and suburban population. Nevertheless, the overall experiences of Mexican Americans in Garden City and Santa Maria are consonant with research conducted on later-generation Mexican Americans in more urban and suburban settings (Macias, 2003(Macias, , 2004(Macias, , 2006Ochoa, 2000Ochoa, , 2004. Furthermore, the experiences of Mexican Americans in this study with regard to intergenerational advancement in education, income, and intermarriage reflect national trends (Alba, 2006;Alba et al, forthcoming;Duncan, Hotz, and Trejo, 2006;Macias, 2006;Perlmann and Waters, 2004;Reed et al, 2005;Smith, 2003Smith, , 2006.…”
Section: Methods Research Setting and Respondentssupporting
confidence: 61%
“…Both these communities are semi-rural, and Mexican Americans are predominantly an urban and suburban population. Nevertheless, the overall experiences of Mexican Americans in Garden City and Santa Maria are consonant with research conducted on later-generation Mexican Americans in more urban and suburban settings (Macias, 2003(Macias, , 2004(Macias, , 2006Ochoa, 2000Ochoa, , 2004. Furthermore, the experiences of Mexican Americans in this study with regard to intergenerational advancement in education, income, and intermarriage reflect national trends (Alba, 2006;Alba et al, forthcoming;Duncan, Hotz, and Trejo, 2006;Macias, 2006;Perlmann and Waters, 2004;Reed et al, 2005;Smith, 2003Smith, , 2006.…”
Section: Methods Research Setting and Respondentssupporting
confidence: 61%
“…Apart from econometric reasons (identification, small samples, etc…), a smaller effect among the Jewish male community can be economically motivated, and thus reconciled with previous findings, by the fact that minority groups extract higher benefits from the same service, given their lower starting point. This is in line with previous findings in the literature (Berger and Hirsch 1983;Phillips et al 1992;Angrist 1998;Hisnanick 2003;Hirsch and Mehay 2003;Macias 2003;Nesbit and Reingold 2011, among others).…”
Section: B Additional Robustness Checkssupporting
confidence: 93%
“…The value of networks is the most stressed aspect of social capital-most importantly the interethnic networks (known as "bridging" in sociological literature). First, the social pressure on minority groups to conform to the dominant culture expectations can be alleviated in the military setting as a professional organization providing key opportunities for interethnic and intraethnic networking (Macias 2003), as Druze men in the army serve along their Jewish counterparts. 19 Furthermore, Annen (2013) showed that social capital can facilitate access to the market and thus substitute for other more costly, formal methods of doing so: this notion pertains to the goods market but can readily be extended to the labor market.…”
Section: Mechanisms and Discussionmentioning
confidence: 99%
“…The promise of upward mobility motivates assimilation into dominant cultural values (Waters, Tran, Kasinitz, & Mollenkopf, 2010). The social pressure to assimilate to dominant culture is still relevant (Macias, 2003) and can affect well-being for adolescents (Greenman & Xie, 2008). Interestingly, assimilation among adolescents is positively associated with academic achievement and psychological well-being as well at-risk behaviors (Xie & Greeman, 2011).…”
mentioning
confidence: 99%